1985
DOI: 10.1111/j.1432-1033.1985.tb09126.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of cell wall synthesis and acylation of the penicillin binding proteins during prolonged exposure of growing Streptococcus pneumoniae to benzylpenicillin

Abstract: Growing cultures of an autolysis‐defective pneumococcal mutant were exposed to [3H]benzylpenicillin at various multiples of the minimal inhibitory concentration and incubated until the growth of the cultures was halted. During the process of growth inhibition, we determined the rates and degree of acylation of the five penicillin‐binding proteins (PBPs) and the rates of peptidoglycan incorporation, protein synthesis, and turbidity increase. The time required for the onset of the inhibitory effects of benzylpen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
32
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 41 publications
(5 reference statements)
2
32
0
Order By: Relevance
“…Earlier studies have shown that bacterial cells can continue cell wall synthesis and growth with less than the total normal complement of wall synthetic enzymes, suggesting that only a subclass of all these proteins detectable by the penicillin-binding technique is actually essential (3,22). We introduced an experimental design that allowed us to further dissect this question.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies have shown that bacterial cells can continue cell wall synthesis and growth with less than the total normal complement of wall synthetic enzymes, suggesting that only a subclass of all these proteins detectable by the penicillin-binding technique is actually essential (3,22). We introduced an experimental design that allowed us to further dissect this question.…”
Section: Discussionmentioning
confidence: 99%
“…shown that apparently normal wall synthesis (and cell multiplication) can continue with less than a full complement of these essential PBPs (3,22), indicating either that these proteins are present in excess or that only some fraction of all the proteins estimated by the PBP assay are functional.…”
mentioning
confidence: 99%
“…The virtually complete inhibition of the maturation process by cefotaxime, a relatively poor inhibitor of PBP 2b, without a comparably severe inhibition of the formation of the nascept wall,'suggests that PBP 2b may perform an important role in this process (i.e., the initial incorporation of precursors into the wall). Such a role has already been suggested for PBP 2b on the basis of earlier studies (27).…”
Section: Discussionmentioning
confidence: 52%
“…The cell wall of this * Corresponding author. bacterium does not seem to undergo turnover (27), and in the case of pneumococci it is possible to design a method that allows a physical separation of newly made from mature cell wall segments which can then be compared for compositional differences by direct chemical analysis.The method is based on the high degree of specificity of the pneumococcal autolysin (N-acetylmuramoyl-L-alanine amidase) in dissecting out wall segments with choline-containing teichoic acid chains from amid wall segments that contain ethanolamine (EA) teichoic acids and are resistant to the hydrolytic action of the amidase (19). In the basic experimental design, we grew pneumococci in EA medium.…”
mentioning
confidence: 99%
See 1 more Smart Citation